2015
DOI: 10.3892/mmr.2015.4346
|View full text |Cite
|
Sign up to set email alerts
|

Licochalcone C induces apoptosis via B-cell lymphoma 2 family proteins in T24 cells

Abstract: The current study investigated the mechanisms by which licochalcone C induces apoptosis of T24 human malignant bladder cancer cells. Cell viability was evaluated using an MTT assay. Apoptosis was investigated using a morphological assay, flow cytometry and a caspase-3 activity assay. Alterations in the gene expression levels of Bcl-2 family members were measured by semi-quantitative reverse transcription-polymerase chain reaction assays. The protein levels of pro-caspase-3 and cleaved poly(ADP ribose) polymera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Normalized intensity of CHOP, DR5 and DR4 versus actin were presented, and their expression levels were significantly increased. CHOP, C/EBP homologous protein; LCC, licochalcone C; ROS, reactive oxygen species as the PTP1B enzyme inhibitory activity, 32 attenuation of inflammatory response, 7 cardio-protective effect, 7,33 and apoptosis, 10 but their mechanisms of action remain elusive. Therefore, we needed to investigate the unidentified effects of LCC, which is a type of natural phenolic agent isolated from licorice on OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Normalized intensity of CHOP, DR5 and DR4 versus actin were presented, and their expression levels were significantly increased. CHOP, C/EBP homologous protein; LCC, licochalcone C; ROS, reactive oxygen species as the PTP1B enzyme inhibitory activity, 32 attenuation of inflammatory response, 7 cardio-protective effect, 7,33 and apoptosis, 10 but their mechanisms of action remain elusive. Therefore, we needed to investigate the unidentified effects of LCC, which is a type of natural phenolic agent isolated from licorice on OSCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] From LC species, LCC is isolated from Glycyrrhiza inflata and has been reported to be potent against bladder cancer cells. 10 Although LC has many beneficial effects in there are a few reports on LCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it attenuated migration, adhesion, and invasion of cancer cells accompanied with the downregulated protein expression of MMP-9 and nuclear translocation of nuclear factor-κB (NF-κB) [115]. Similar to licochalcone B, licochalcones C and D induced apoptosis by altering the expression of Bcl-2 family member genes and activating the caspase-mediated cell death signaling pathway [45,46]. Meanwhile, licochalcone D induced apoptosis through mitochondrial pathway and blocked cell migration and invasion into surrounding tissues by reducing the activity and expression of MMP-2 and MMP-9 [46].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Numerous flavonoids in traditional Chinese herbs may be promising candidates for the development of novel anticancer drugs ( 3 ). Previously, we found that Licochalcone C induced apoptosis via B-cell lymphoma 2 family proteins in T24 cells ( 4 ). Licochalcone A induced T24 bladder cancer cell apoptosis by increasing intracellular calcium levels ( 5 ).…”
Section: Introductionmentioning
confidence: 98%